PEMBENTUKAN PENYULUH SEBAYA GUNA PENINGKATAN PENGETAHUAN PELAJAR SMA TERKAIT PENCEGAHAN COVID-19 DI KOTA YOGYAKARTA - Amaze Grace SIra; Septian Dewi Periska; Patricia Dissy Andrea (Servirisma, 2022)
Covid-19 has spread to various countries around the world, including Indonesia. The government has implemented many regulations related to preventing Covid-19, with 5M: wearing masks, washing hands with soap and running water, maintaining distance, staying away from crowds, and limiting mobilization and interaction as well as efforts to accelerate Covid-19 vaccinations. By empowering a group of teenagers who are aware of the importance of the Covid-19 vaccine, these teenagers can become role models in providing information to their peers. The purpose of this Community Service Program is to form peer educators be a  role models for youth to increase their knowledge of 5 M and Covid-19 vaccinations. The theme that was carried was “Prajurit X Corona”. The method used is to conduct field observations in four high schools in Yogyakarta and communicate with schools to selecting 4 students who will be fostered as peer educators. Conducted training for peer extension workers with the topic of Covid-19, 5M programe and Covid-19 Vaccination and Public Speaking. After the activity was carried out, it was conveyed that the students felt helped by this training.